Transformational Leadership as a Key Factor in Improving the Performance of Healthcare Organizations - Dewi Agustina; Restu Rahayani Padang; Tia Wahyuni Dolok Saribu; Karin; Ririn Hasrat Kartika Zalukhu; Nabilla Suci Ramadhani; Silvya Rahma; Muhammad Ramadhan Ginting; Sofia Nabila; Siti Nurhamidah Harahap; Zahra Dwi Andini; Aprilyautami; Susan Limbong (Universitas Muhammadiyah Palu, 2025)
The performance of healthcare organizations is significantly influenced by the quality of leadership applied. This study aims to comprehensively examine the role of transformational leadership in improving healthcare organizational performance through a systematic literature review approach. The literature search was conducted through Google Scholar, PubMed, ScienceDirect, and ResearchGate using the keywords